Efektivitas Platform Wordwall pada Pembelajaran PAI di Madrasah Aliyah Negeri (MAN) pada Masa Pandemi - Burhanudin Ata Gusman; Unik Hanifah Salsabila; Hoerotunnisa; Lesta Yahsa Giardi; Viki Fadhila (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2021)
Learning problems during the pandemic become heavy, such as in learning activities, students will feel bored if the material delivered by educators is monotonous. To prevent this, educators must have the capability to determine learning materials in such a way so that there are innovations that make students more enthusiastic and have an interest in learning. This study aimed to evaluate the effectiveness of the word wall application in teaching and learning activities during the Covid-19 pandemic at MAN 4 Kebumen. The method used is quantitative and qualitative and is supported through observation and interviews to obtain research data. The results of this study are based on student learning outcomes from meetings I to III have shown outstanding results, where the score of Islamic religious education tests by students of MAN 4 Kebumen has an average value of 88.04 with a percentage of completeness of 80.35%, which includes an outstanding category. That can conclude that the word wall application is very effective in increasing student learning outcomes and supporting student motivation at Madrasah Aliyah Negeri 4 Kebumen.